Comparative Legal Analysis of the Experience of Foreign Countries on Issues of Inheritance by Will (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
A distinctive feature of the modern world is integration processes affecting various spheres of international and domestic life. The migration of people from one country to another is the reason for the emergence of various legal relations, among which inheritance relations occupy an important place. The number of inheritance cases involving foreigners is increasing every year. In the modern world, the main factors contributing to the emergence of hereditary ties with foreign elements are: marriages with foreigners, acquisition of dual citizenship, international investment processes, economic and linguistic connections of regions, etc.